The Harlem Hellfighters - Brooks, Max 1972- (Broadway Books, 2014)
"From bestselling author Max Brooks, the riveting story of the highly decorated, barrier-breaking, historic black regiment...the Harlem Hellfighters. The Harlem Hellfighters is a fictionalized account of the 369th Infantry Regiment...the first African American regiment mustered to fight in World War I. From the enlistment lines in Harlem to the training camp at Spartanburg, South Carolina, to the trenches in France, bestselling author Max Brooks tells the thrilling story of the heroic journey that these soldiers undertook for a chance to fight for America. Despite extraordinary struggles and discrimination, the 369th became one of the most successful...and least celebrated...regiments of the war. The Harlem Hellfighters, as their enemies named them, spent longer than any other American unit in combat and displayed extraordinary valor on the battlefield. Based on true events and featuring artwork from acclaimed illustrator Caanan White, these pages deliver an action-packed and powerful story of courage, honor, and heart"...
Includes bibliographical references (pages 247-250)
Keywords: United States -- Army -- Infantry Regiment, 369th -- Comic books, strips, etc; United States -- Army -- Infantry Regiment, 369th -- Juvenile literature; United States -- Army -- African American troops -- History -- 20th century -- Comic books, strips, etc; United States -- Army -- African American troops -- History -- 20th century -- Juvenile literature; USA -- Army; Geschichte 1900-2000; HISTORY / Military / World War I.; COMICS & GRAPHIC NOVELS / Literary; Geschichte; Weltkrieg (1914-1918); World War, 1914-1918 -- Participation, African American -- Comic books, strips, etc; World War, 1914-1918 -- Participation, African American -- Juvenile literature; African American soldiers -- History -- 20th century -- Comic books, strips, etc; African American soldiers -- History -- 20th century -- Juvenile literature; Infanterie; Schwarze; Erster Weltkrieg; Soldat; Sachcomic; USA; Graphic novels; Comic